Supply and demand relationship of ecosystem services from the perspective of hydropower development. Issue 1 (March 2023) - Zhang, Yu; Fu, Bin; Zhu, Xiaokang; Donyu, Dorjee
The supply and demand of ecosystem services is a popular research topic, however, studies on ecosystem services related to hydropower are rare. We selected hydropower stations in the Lhasa River of the Qinghai-Tibet Plateau as the beneficiaries of hydropower development. We then identified three ecosystem services. We assessed the supply of ecosystem services and the demand of hydropower for them. Finally, we discussed the relationship between hydropower and watersheds. The results demonstrated the following: (1) Water yield was 309.0 ± 110.3 mm, with a decreasing spatial pattern from the northeast to the southwest. Soil conservation was 119.2 ± 224.6 t/(hm 2 ⋅a), with a spatial pattern that was high in the southeast and low in the northwest. Flood mitigation was 21.3 ± 2.9 mm, and the lower values were in lower elevation areas. (2) Hydropower has produced demands for the three services. The demand for the water yield of the five stations was 0.45 × 10 8 m 3 − 1.64 × 10 8 m 3 . The demand for soil conservation from the Pangduo and Zhikong stations were 7.87 and 4.53 times their storage capacity, respectively. The demand for the flood mitigation of these two stations were 1.49 times and 1.09 times that of their flood regulation storage capacities. (3) The supply of the water yield service was greater than the demand for nearly the entire year, with an ecosystem supply and demand index between 4.73 and 14.06. The supply and demand of soil conservation services was nearly balanced. The flood mitigation service provided by the upstream ecosystem of Pangduo was 70.18 times the demand and 20.58 times the service of Zhikong. The results demonstrated that hydropower has a strong dependence on ecosystem services. This indicated that both enhancement and mitigation should be considered in the design payment of ecosystem service roles.